Pengaruh Model Pembelajaran Kooperatif Tipe Round Table Terhadap Kemampuan Komunikasi Matematis Siswa SMAN 101 Jakarta - Belva Yessica Grace Morainauli (Program Studi Pendidikan Matematika FMIPA Universitas Negeri Jakarta, 2019)
This study aims to determine whether the Round Table cooperative learning model influences the mathematical communication skills of students of SMAN 101 Jakarta. This research was conducted in the even semester of the 2018/2019 academic year on the subject of Lines and Series. The research method used was quasi-experimental. The target population of this study were all students of SMAN 101 Jakarta and the affordable population in this study were students of XI MIPA. The sampling technique uses cluster random sampling technique. The research instrument used was a test of mathematical communication skills as many as four description questions. the instrument has gone through content validation tests, construct validation and empirical validation. After the instrument is valid, reliability is tested where the correlation coefficient obtained is 0.5602. After testing the normality, homogeneity and similarity of averages and cluster random sampling. XI MIPA 2 was chosen as the control class and XI MIPA 4 as the experimental class. Based on the calculation of the research data of the two classes, each of them is normally distributed and has the same or homogeneous variance. Therefore, hypothesis testing is done by using t-test statistics with a significant level Î± = 0.05. Based on the results of the test, the value of tcount = 2.43499 and t table = 1.6682 is obtained, so that it gets tcount> ttable. So reject H0. This shows that there is the influence of Round Table cooperative learning model on mathematical communication skills of students of SMAN 101 Jakarta.